Mycobacterium chelonae Is an Ubiquitous Atypical Mycobacterium - Miguel Pinto-Gouveia; Ana Gameiro; Leonor Ramos; José Carlos Cardoso; Maria Manuel Brites; Óscar Tellechea; Américo Figueiredo (Karger Publishers, 2015)
The type of cutaneous infection varies mainly according to the patient's immune status, and the disseminated form is mostly found in the context of immunosuppression. We report the case of a 62-year-old male who was under long-term systemic corticosteroid therapy and presented with a 7-month history of multiple painless cutaneous lesions at various stages of development: papules, nodules, pustules and hemorrhagic crusts, as well as small erosions and ulcers distributed over the limbs and scalp. Cutaneous biopsy showed a suppurative granulomatous infiltrate with abscess formation. Fite stain revealed numerous extracellular bacilli, suggesting mycobacterial infection, particularly by atypical mycobacteria. Culture of a skin sample revealed Mycobacterium chelonae. The patient started multidrug therapy and showed clinical improvement despite of resistance to one of the antibiotics. This striking presentation underlines the role of immunosuppression with corticotherapy as a major risk factor for these infections. Multidrug therapy is advised and antibiogram is essential in directing treatment.